Profil Penalaran Matematis Siswa Berdasarkan Gaya Kognitif Reflektif dan Impulsif - Faisal Faisal; Srimuliati Srimuliati; Khairatul Ulya; Leni Damayanti (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
Every student has different style in understanding a concept of learning. The different style of learning is called students’ uniqueness and it is influenced cognitive style of students themselves. Cognitive style is clearly seen when students receive mathematical concept that requires good reasoning abilities. This study aims to determine how students process information and reasoning given based on cognitive styles in this case reflective and impulsive cognitive style. The subjects of this study were students of grade XI MAS Al-Jami'atul Washliyah Stabat. Through the stages of the MFFT (Matching Familiar Figure Test), two students were selected, each with a reflective and impulsive cognitive style. The two students were given mathematical reasoning tests questions on trigonometry concept and afterward conducted interviews to deepen the data. Data were analysed using triangulation, data reduction, data presentation and verification. The results of the study showed that in doing the tests given, students with a reflective style tend to be thorough and correct with a longer duration of time than students with an impulsive style, and vice versa.